Penyerahan Protokol Notaris Yang Telah Meninggal Dunia Kepada Notaris Penerima Protokol Serta Prakteknya Di Indonesia - Yunizcha Mohamad Putri Limbanadi (Officium Notarium, 2024)
The aim of the research is to find out and analyze the procedures for submitting protocols to Notaries who are declared dead. The type of research in this research is normative, where an assessment of applicable laws and regulations is carried out. The results of the research concluded that: (1) Submission of the Notary's protocol for declaring death to another Notary as the recipient of the protocol is carried out no later than 30 days by making an official report on the submission of the Notary's protocol which is approved by the Notary's heirs and the recipient of the protocol must be the notary public; (2) The legal position of the Notary who receives the Notary's protocol dies is limited to receiving and keeping the protocol. If there is a legal problem, the notary responsible is the notary relating to the deed; (3) Handing over a deceased Notary's protocol to the recipient Notary is also the authority of the MPD, if the Notary's protocol is not given to the recipient's Notary within 30 days, then the MPD has the authority to take the protocol and hand it over to the Notary receiving the protocol.Keywords: Notary Protocol; Notary Dies AbstrakTujuan penelitian untuk mengetahui, menganalisis bagaimana prosedur penyerahan protokol Notaris yang dinyatakan meninggal. Jenis penelitian dalam penelitian ini adalah normatif dimana dilakukan pengkajian peraturan perundang-undangan yang berlaku. Hasil penelitian menyimpulkan bahwa: (1) Penyerahan protokol Notaris dinyatakan meninggal kepada Notaris lain selaku penerima protokol dilaksanakan paling lama 30 hari dengan membuat berita acara penyerahan protokol Notaris yang disetujui oleh ahli waris Notaris dan yang menerima protokol tersebut harus notaris penerima; (2) Kedudukan hukum Notaris yang menerima protokol Notaris meninggal dunia sebatas menerima dan menyimpan protokol tersebut. Apabila terdapat masalah hukum yang bertanggung jawab adalah Notaris yang berkaitan dengan akta tersebut; (3) Penyerahan protokol Notaris yang sudah meninggal kepada Notaris penerima juga kewenangan MPD, jika protokol Notaris tidak diberikan ahli waris kepada Notaris penerima dalam 30 hari maka MPD berwenang mengambil protokol tersebut dan diserahkan pada Notaris penerima protokol.Kata kunci: Protokol Notaris; Notaris Meninggal Dunia.